Pattern synthesis method for arbitrary arrays with desired mainloble response - Dian-fei PAN; Nai-ping CHENG (Tongxin xuebao)
A pattern synthesis method based on adaptive array theory and convex optimization principle was proposed for arbitrary arrays,especially considering the influence of different orientation on array pattern.Firstly,the array pattern with special sideloble shape is obtained by adaptive array theory method; and then,the mainloble pointing to 0° is taken as reference to determine the pattern mainloble with variant steering angle.Finally,the optimal array pattern synthesis with desired mainloble response is converted to a second-order cone programming problem.The resulting optimization problem is nonconvex and is implemented via iterative algorithms of convex optimization,which can be solved using the second-order cone programming method at each iteration.Taking the method developed can obtain satisfied mainlobe response and less synthesized error in sideloble region.Theoretical analyses and simulation results show that the synthe-sized pattern has the same mainloble performance as the desired mainlabole in different orientation,and also the sideloble can maintain the shape to suppress the dynamic interference.